Modulatory effects of Aqueous extract from Tetracarpidium conophorum leaves on key enzymes linked to erectile dysfunction and oxidative stress-induced lipid peroxidation in penile and testicular tissues - Seun Akomolafe, Ganiyu Oboh, Tosin Olasehinde, Sunday Oyeleye & , Opeyemi Ogunsuyi & (Journal of Applied Pharmaceutical Science, 2017)
Tetracarpidium conophorum (walnut) is used in folk medicine for the treatment of erectile dysfunction but the mechanism remains unclear. This study evaluated the effect of aqueous extract from T. conophorum leaves on oxidative stress-induced penile damage and key enzymes linked to erectile dysfunction. The inhibitory effect of the extract on sodium nitroprusside (SNP)-induced lipid peroxidation, arginase, angiotensin I-converting enzyme (ACE) and acetylcholinesterase (AChE) activities in penile and testicular tissue homogenates were determined via colorimetric method. The aqueous extract inhibited SNP-induced lipid peroxidation in rats penile and testicular homogenates in a dose dependent manner. The highest inhibitory effect was obtained in the penis at a concentration of 0.5 mg/mL. Furthermore, the extract inhibited arginase activity in a dose dependent pattern. The IC50 revealed that the extract had significantly (P
Keywords: Tetracarpidium conophorum, erectile dysfunction, arginase, angiotensin-I converting enzyme, acetylcholinesterase